2003
DOI: 10.1021/jp0343584
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Single-Crystal-Type EPR Spectra from Monolayers of Copper-Exchanged Zeolite Na-A Crystals Assembled on Glass Plates

Abstract: Single-crystal-type EPR spectra were observed for microcrystals of copper(II)-exchanged zeolite Na-A assembled on glass plates when the magnetic field was perpendicular to the glass surface. Two copper species (H and D) were identified both in the powder sample and in the assembled crystals. The g z direction of species H is parallel to [001] of the cubic crystal, while that of species D is tilted 9°away from [001]. Previously, other authors assumed the g z directions of the two corresponding species to be par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The substrates that have been tested so far are glass, ,,, ,,− glass fiber, silica, alumina, large zeolite, vegetable fibers (cotton, linen, and hemp) (Figure ), artificial fibers (nylon and polyester), and conducting substrates (Pt, Au, and ITO glass) 9 SEM images of a nano-zeolite-Y-coated cotton fiber …”
Section: Types Of Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The substrates that have been tested so far are glass, ,,, ,,− glass fiber, silica, alumina, large zeolite, vegetable fibers (cotton, linen, and hemp) (Figure ), artificial fibers (nylon and polyester), and conducting substrates (Pt, Au, and ITO glass) 9 SEM images of a nano-zeolite-Y-coated cotton fiber …”
Section: Types Of Substratesmentioning
confidence: 99%
“…Using zeolite microcrystals as model microbuilding blocks, we developed methods of organizing them into two- (2D) and three-dimensionally (3D) organized structures. The use of zeolite microcrystals as microbuilding blocks has additional merit since each zeolite microcrystal has millions of regularly spaced nanochannels and billions of nanopores which can be filled with a variety of functional molecules or nanoparticles. Therefore, we intended to not only develop the ‘chemistry of microbuilding blocks' but also open a gateway to application of zeolites as advanced materials.…”
Section: Introductionmentioning
confidence: 99%
“…We have been interested in extracting information on molecular orientation from EPR spectra of partially oriented systems. Recently some of us observed single-crystal-type EPR spectra from monolayers of copper-exchanged zeolite Na-A microcrystals assembled on glass plates and obtained information on the orientations of the copper species . The monolayers consisted of small domains in which microcrystals were oriented in the same direction, but the domains were randomly oriented on the glass surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently some of us observed single-crystal-type EPR spectra from monolayers of copper-exchanged zeolite Na-A microcrystals assembled on glass plates and obtained information on the orientations of the copper species. 1 The monolayers consisted of small domains in which microcrystals were oriented in the same direction, but the domains were randomly oriented on the glass surface. So, although it was a partially oriented system, it produced a single-crystal-type spectrum when the magnetic field was perpendicular to the glass surface.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature EPR studies on LB films of bis-radicals substituted benzene with long alkyl chain found antiferromagnetic properties in these layers. 16 So et al 17 reported single-crystal-like EPR spectra that were obtained from monolayers of copper-exchanged zeolite Na-A (Cu/NaA) microcrystals on glass plates. From these measurements the g zz direction of two copper species in zeolite Na-A were determined.…”
Section: Introductionmentioning
confidence: 99%